Best approximations of the classes $B_{p,\,θ}^{r}$ of periodic functions of many variables in uniform metric - Romanyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We obtain estimates exact in order for the best approximations of the classes $B_{∞,\,θ}^{r}$ of periodic functions of two variables in the metric of $L_{∞}$ by trigonometric polynomials whose spectrum belongs to a hyperbolic cross. We also investigate the best approximations of the classes $B_{p,\,θ}^{r},\quad 1 ≤ p < ∞$, of periodic functions of many variables in the metric of $L_{∞}$ by trigonometric polynomials whose spectrum belongs to a graded hyperbolic cross.